2013
DOI: 10.1080/15287394.2013.826569
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Aflatoxin B1in Swine Production and Possible Contamination Sources

Abstract: Although the adverse health consequences of ingestion of food contaminated with aflatoxin B1 (AFB1) are known, relatively few studies are available on the adverse effects of exposure in occupational settings. Taking this into consideration, our study was developed aiming to elucidate the possible effects of occupational exposure to AFB1 in Portuguese swine production facilities using a specific biomarker to assess exposure to AFB1. In total, 28 workers participated in this study, providing blood samples, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 34 publications
1
52
1
Order By: Relevance
“…Although there are differing proportions of AFB 1 , AFB 2 , AFG 1 , and AFG 2 in Aspergillus-contaminated feed, aflatoxinogenic molds predominantly produce AFB 1 and to a lesser extent the other three AF in feed (Cervino et al, 2008;Joubrane et al, 2011;Li et al, 2009). Worldwide, occupational exposure to AF is alarming; a level of even $8 ng AFB 1 /ml in blood of swine 'workers' whose exposure was by the inhalation, oral, and/or dermal routes, has been reported (Viegas et al, 2013). Further, in countries where mycotoxin-monitoring programs are absent, livestock may encounter far higher levels of the AF than the doses used here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are differing proportions of AFB 1 , AFB 2 , AFG 1 , and AFG 2 in Aspergillus-contaminated feed, aflatoxinogenic molds predominantly produce AFB 1 and to a lesser extent the other three AF in feed (Cervino et al, 2008;Joubrane et al, 2011;Li et al, 2009). Worldwide, occupational exposure to AF is alarming; a level of even $8 ng AFB 1 /ml in blood of swine 'workers' whose exposure was by the inhalation, oral, and/or dermal routes, has been reported (Viegas et al, 2013). Further, in countries where mycotoxin-monitoring programs are absent, livestock may encounter far higher levels of the AF than the doses used here.…”
Section: Discussionmentioning
confidence: 99%
“…The AF and their toxic effects on key immune cells is a threat to animal and human health worldwide (CAST, 1989;Luongo et al, 2013;Reddy et al, 2009;Viegas et al, 2013). Recent data indicate that the chronic exposure of piglets to low mycotoxin levels still could affect the intestinal immune system and prolong infection with intestinal pathogens (Devriendt et al, 2009;Oswald et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As such, routine harsher monitoring of AFs levels in different feedstuffs is urgent in semiarid northeastern Iran. For the detection of AFB 1 and AFM 1 , herein we used ELISA with sensitivity and specificity of above 98% with acceptable recovery rate, LOD/LOQ, and precision; nevertheless it is worth simultaneously confirming their quantification with some more advanced analytical tool like HPLC or LC/MS/MS as done by others [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, pivotally food animals increasingly consume aflatoxigenic mold-contaminated feed, worldwide [5,7,10]. Advanced analytical methods on AFB 1 /M 1 detection have revealed that even in Europe AFs routinely circulate in the body of food-producing animals and humans through feed/foods [12,13]. Predominantly hydroxylated AFB 1 metabolite (AFM 1 ) is as carcinogen as AFB 1 and bioaccumulates everywhere (meat, milk, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Both markers of internal and effective dose are therefore preferable to measuring external levels of the compound in question (for example in the workplace), as they take into account biological variations in absorption, metabolism and distribution of the compound between individuals [15,17]. Other examples of applications in occupational contexts are the recent publications regarding exposure to Aflatoxin B1 in several settings [20][21][22][23]. The use of an exposure biomarker demonstrates that occupational exposure is occurring in specific settings, even when exposure to this natural toxin is recognized to occur essentially through food consumption.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%